2014
DOI: 10.3389/fnana.2014.00049
|View full text |Cite
|
Sign up to set email alerts
|

Complementary expression of EphA7 and SCO-spondin during posterior commissure development

Abstract: Bilaterally symmetric organisms need to exchange information between the two sides of their bodies in order to integrate sensory inputs and coordinate motor control. This exchange occurs through commissures formed by neurons that project axons across the midline to the contralateral side of the central nervous system. The posterior commissure is the first transversal axonal tract of the embryonic vertebrate brain. It is located in the dorsal portion of the prosomere 1, at the caudal diencephalon. The axons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…First, the axons run dorsally toward the lateral roof plate. In this step, studies performed in chick embryos revealed that axons are surrounded by EphA7-expressing cells that appear to form a repulsion barrier that delimits the axonal trajectory (Stanic et al, 2014 ). Second, in the lateral roof plate the presence of SCO-spondin and slit2 in chick and Xenopus leavis embryos respectively promote fasciculation and drive the axons to the midline (Stanic et al, 2010 ; Tosa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the axons run dorsally toward the lateral roof plate. In this step, studies performed in chick embryos revealed that axons are surrounded by EphA7-expressing cells that appear to form a repulsion barrier that delimits the axonal trajectory (Stanic et al, 2014 ). Second, in the lateral roof plate the presence of SCO-spondin and slit2 in chick and Xenopus leavis embryos respectively promote fasciculation and drive the axons to the midline (Stanic et al, 2010 ; Tosa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, at the midline, axons either turn to the ipsilateral side or continue to the opposite side. Worth noting, a set of EphA7-expressing cells at the midline seems critical in the axonal decision process (Stanic et al, 2014 ). The relevance of the caudal diencephalic roof plate in guiding the PC axons is also sustained by data from various null mutant mice (mutant for pax2/5, pax6, msx 1 ), which display a wide range of abnormalities in the diencephalic roof plate and fail to form a normal PC (Schwarz et al, 1999 ; Louvi and Wassef, 2000 ; Estivill-Torrus et al, 2001 ; Fernandez-Llebrez et al, 2004 ; Ramos et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…EphA7 is widely expressed in embryonic tissues, especially developing central nervous system [18]. A previous study disclosed that the EphA7 receptor regulates apoptosis during early brain development.…”
Section: Introductionmentioning
confidence: 99%
“…However, abnormality in the PC has not been reported in other amniotes including slit or robo mutant mice [ 27 , 28 , 30 ]. It may be due to the fact that the disruption of slit or robo signaling may be compensated for by other paralogues or guidance molecules, such as the EphA7-dependent system which is involved in the formation of the chick PC [ 55 ]. Thus, further functional studies using vertebrate groups should be necessary to identify the evolutionary process of PC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown whether there is a direct link between the PC and swimming behavior, it is important to note that axons in the PC stem from several types of neurons. Previous studies have shown that the PC contains axons that stem from several nuclei, including the nTPC [ 46 , 55 ]. In mammals, the PC is involved in oculomotor movement by transmitting visual information coming from the cerebral cortex (visual area) and superior colliculus [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%